The role of organizational justice as mediator in the relationship between Islamic work ethics and work engagement - Nindyati, Ayu Dwi; Ulfia, Nida (Humanitas: Indonesian Psychological Journal, 2024)
This research aims to examine organizational justice's role as a mediator in the association between Islamic work ethic and work engagement among Sharia Bank employees. The respondents were 86 employees of Sharia Bank in Jakarta. The hypothesis was examined through a mediation test that involved four steps, including three simple regression and multiple regression. The results showed that organizational justice meditates the relationship between Islamic work ethic and work engagement among Sharia Bank employees. Employees who strongly uphold Islamic work ethics will have a positive perception of organizational justice, which, in turn, leads to higher engagement with their work. These findings have implications on how organizations can enhance employees' work engagement by promoting employees' positive perception of organizational justice.